Traceless Removal of Two Kernel Atoms in a Gold Nanocluster and Its Impact on Photoluminescence. (8th March 2021) - Zhou, Yue; Liao, Lingwen; Zhuang, Shengli; Zhao, Yan; Gan, Zibao; Gu, Wanmiao; Li, Jin; Deng, Haiteng; Xia, Nan; Wu, Zhikun
Abstract: Removing or adding kernel atoms of metal nanoclusters (NCs) without leaving a trace is a substantial challenge because the kernel atoms are inside and covered by the outer staples. However, such kernel tuning is very important for improving the properties and acquiring an in‐depth understanding of the kernel‐property correlation. Photoluminescence (PL) is one of the most intriguing characteristics of metal NCs but has not been well understood until now. Inspired by these challenges/questions, we conducted this study and, for the first time, achieved the traceless removal of two kernel atoms in a gold nanocluster by applying a simple thermal treatment and revealed its impact on PL. Further, we demonstrated that the kernel Au‐Au bond length can be an indicator for a comparison of the PL or kernel charge state between nanoclusters with similar kernel structures and sizes. Abstract : Two novel nanoclusters Au48 (m‐MB)26 and Au46 (m‐MBT)26 have been synthesized and fully characterized, and the traceless removal of two kernel atoms in metal nanoclusters has been achieved for the first time. The two kernel atoms reduction leads to the photoluminescence quantum yield (QY) increase by almost four times. In addition, kernel bond length dependent photoluminescence and kernel charge state were first revealed.